The Mopra Southern Galactic Plane CO Survey—Data Release 3. (17th August 2018) - Braiding, Catherine; Wong, G. F.; Maxted, N. I.; Romano, D.; Burton, M. G.; Blackwell, R.; Filipović, M. D.; Freeman, M. S. R.; Indermuehle, B.; Lau, J.; Rebolledo, D.; Rowell, G.; et al.
Abstract: We present observations of 50 deg 2 of the Mopra carbon monoxide (CO) survey of the Southern Galactic Plane, covering Galactic longitudes l = 300–350° and latitudes | b | ⩽ 0.5°. These data have been taken at 0.6 arcmin spatial resolution and 0.1 km s −1 spectral resolution, providing an unprecedented view of the molecular clouds and gas of the Southern Galactic Plane in the 109–115 GHz J = 1–0 transitions of 12 CO, 13 CO, C 18 O, and C 17 O. We present a series of velocity-integrated maps, spectra, and position-velocity plots that illustrate Galactic arm structures and trace masses on the order of ~10 6 M⊙ deg −2, and include a preliminary catalogue of C 18 O clumps located between l = 330–340°. Together with the information about the noise statistics of the survey, these data can be retrieved from the Mopra CO website and the PASA data store.